Strategies to improve recruitment to randomised controlled trials. - Treweek, S; Pitkethly, M; Cook, J; Kjeldstrøm, M; Taskila, T; Johansen, M; Sullivan, F; Wilson, S; Jackson, C; Jones, R; Mitchell, E (2010)
BACKGROUND: Recruiting participants to trials can be extremely difficult. Identifying strategies that improve trial recruitment would benefit both trialists and health research. OBJECTIVES: To quantify the effects of strategies to improve recruitment of participants to randomised controlled trials. SEARCH STRATEGY: We searched the Cochrane Methodology Review Group Specialised Register - CMR (The Cochrane Library (online) Issue 1 2008) (searched 20 February 2008); MEDLINE, Ovid (1950 to date of search) (searched 06 May 2008); EMBASE, Ovid (1980 to date of search) (searched 16 May 2008); ERIC, CSA (1966 to date of search) (searched 19 March 2008); Science Citation Index Expanded, ISI Web of Science (1975 to date of search) (searched 19 March 2008); Social Sciences Citation Index, ISI Web of Science (1975 to date of search) (searched 19 March 2008); and National Research Register (online) (Issue 3 2007) (searched 03 September 2007); C2-SPECTR (searched 09 April 2008). We also searched PubMed (25 March 2008) to retrieve "related articles" for 15 studies included in a previous version of this review. SELECTION CRITERIA: Randomised and quasi-randomised controlled trials of methods to increase recruitment to randomised controlled trials. This includes non-healthcare studies and studies recruiting to hypothetical trials. Studies aiming to increase response rates to questionnaires or trial retention, or which evaluated incentives and disincentives for clinicians to recruit patients were excluded. DATA COLLECTION AND ANALYSIS: Data were extracted on the method evaluated; country in which the study was carried out; nature of the population; nature of the study setting; nature of the study to be recruited into; randomisation or quasi-randomisation method; and numbers and proportions in each intervention group. We used risk ratios and their 95% confidence intervals to describe the effects in individual trials, and assessed heterogeneity of these ratios between trials. MAIN RESULTS: We identified 27 eligible trials with more than 26,604 participants. There were 24 studies involving interventions aimed directly at trial participants, while three evaluated interventions aimed at people recruiting participants. All studies were in health care. Some interventions were effective in increasing recruitment: telephone reminders to non-respondents (RR 2.66, 95% CI 1.37 to 5.18), use of opt-out, rather than opt-in, procedures for contacting potential trial participants (RR 1.39, 95% CI 1.06 to 1.84) and open designs where participants know which treatment they are receiving in the trial (RR 1.25, 95% CI 1.18 to 1.34). However, some of these strategies have disadvantages, which may limit their widespread use. For example, opt-out procedures are controversial and open designs are by definition unblinded. The effects of many other recruitment strategies are unclear; examples include the use of video to provide trial information to potential participants and modifying the training of recruiters. Many studies looked at recruitment to hypothetical trials and it is unclear how applicable these results are to real trials. AUTHORS' CONCLUSIONS: Trialists can increase recruitment to their trials by using the strategies shown to be effective in this review: telephone reminders; use of opt-out, rather than opt-in; procedures for contacting potential trial participants and open designs. Some strategies (e.g. open trial designs) need to be considered carefully before use because they also have disadvantages. For example, opt-out procedures are controversial and open designs are by definition unblinded.